A comparative investigation on motion model of rifle bullet penetration into gelatin. (May 2017) - Liu, Kun; Ning, Jianguo; Wu, Zhilin; Ren, Huilan; Jiang, Mingfei
Highlights: A motion model that considers both horizontal and normal directions is proposed. The proposed model is based on the motion characteristics of a rifle bullet in gelatin and considers the properties of gelatin and the difference between the attack and yaw angles. The model considers the effect of lift and yaw damping moment. The model parameters are associated with the bullet's design parameters. Abstract: Gelatin is a popular tissue simulant in biomedical applications. The behavior of a bullet and the effects of penetrating a simulant are similar in biological tissue. In order to accurately describe the interaction between a rifle bullet and muscle tissue, this paper discusses the wounding mechanism and the difference between the Bo Janzon (B-J) model, the Karl Sellier (K-S) model, and a three-degree of freedom (DOF) rigid-body motion model previously established by us based on the properties of gelatin. In addition, experiments conducted into rifle bullet penetration into gelatin, with bullet sizes 7.62 × 54 mm and 5.8 × 42 mm, and acquisition of the corresponding motion law are discussed. Numerical calculations reveal that the motion model has a better fit with experimental values than the B-J and K-S models. Further, it more accurately describes the motion of a rifle bullet penetrating gelatin than the other models and also has good generality. Thus, it can provide a theoretical reference for small arms ammunition design and wound treatment.